PENGAKUAN TERHADAP PIHAK NON-ADVOKAT DALAM PEMBERIAN BANTUAN HUKUM (Politik Hukum Bantuan Hukum Dalam Peraturan Perundang-Undangan Di Indonesia) - Adicahya, Akmal (Jurnal Hukum dan Peradilan, 2017)
Access to justice is everyone rights that have to be fulfilled by the government. The regulation number 16 year 2011 of legal aid is an instrument held by the government to guarantee the right. The regulation allowed the participation of non-advocates to provide the legal aid. Through this policy, government emphasizes that:1) Indonesia is a state law which legal aid is an obliged instrument; 2) the prohibition of non-advocate to participate in legal aid is not relevant due to inadequate amount of advocate and citizen seek for justice (justiciabelen), and the advocate is not widely extended throughout Indonesia; 3) Non-Advocates, especially lecturer and law student are widely spread; 4) there are no procedural law which prohibits non-advocate to provide a legal aid. Those conditions are enough argument for government to strengthen the participation of non-advocates in providing legal aid. Especially for The Supreme Court to revise The Book II of Guidance for Implementing Court’s Job and Administration.Keywords: legal aid, non-advocate, justice